Analysis of Customer Satisfaction towards Customer Loyalty of Courier Service Industry Among UTHM Students - Divyasri Ponnusamy; Ramasamy, Chandrashekar (Research in Management of Technology and Business, 2024)
The courier services business is growing quickly and is at the cutting edge of the transportation field. However, the courier service acknowledges the significance of customer satisfaction and brand loyalty when evaluating consumer buying patterns for long-term success. This study proposes to identify the level of customer satisfaction attribute in courier service among UTHM students and to identify the level of customer loyalty of courier service among UTHM students. Other than that, to identify the relationship between the customer satisfaction and customer loyalty in courier service one of the objectives that need to be revised. This study was conducted among University Tun Hussein Onn Malaysia students. The survey method will be employed in a quantitative research approach. The Statistical Package for Social Sciences (SPSS) version 27 and Microsoft Excel are utilized to analyse the data. Furthermore, the results confirmed a significant effect of the accuracy of delivery, price of delivery, information quality, ease of payment, security of payment and customer satisfaction towards courier service industry. According to the findings, the research highlights how crucial it is to the courier service providers to enhance their service to increase customer loyalty and customer satisfaction. Additionally, by engaging with and addressing feedback from customers is essential for establishing trust and confidence in the courier service company’s dedication to customer satisfaction.